Endovascular therapy versus intravenous thrombolysis in cervical artery dissection ischemic stroke – Results from the SWISS registry. (March 2018) - Traenka, Christopher; Jung, Simon; Gralla, Jan; Kurmann, Rebekka; Stippich, Christoph; Simonetti, Barbara Goeggel; Gensicke, Henrik; Mueller, Hubertus; Lovblad, Karl; Eskandari, Ashraf; Puccinelli, Francesco; Vehoff, Jochen; et al.
Introduction: In patients with stroke attributable to cervical artery dissection, we compared endovascular therapy to intravenous thrombolysis regarding three-month outcome, recanalisation and complications. Materials and methods: In a multicentre intravenous thrombolysis/endovascular therapy-register-based cohort study, all consecutive cervical artery dissection patients with intracranial artery occlusion treated within 6 h were eligible for analysis. Endovascular therapy patients (with or without prior intravenous thrombolysis) were compared to intravenous thrombolysis patients regarding (i) excellent three-month outcome (modified Rankin Scale score 0–1), (ii) symptomatic intracranial haemorrhage, (iii) recanalisation of the occluded intracranial artery and (iv) death. Upon a systematic literature review, we performed a meta-analysis comparing endovascular therapy to intravenous thrombolysis in cervical artery dissection patients regarding three-month outcome using a random-effects Mantel–Haenszel model. Results: Among 62 cervical artery dissection patients (median age 48.8 years), 24 received intravenous thrombolysis and 38 received endovascular therapy. Excellent three-month outcome occurred in 23.7% endovascular therapy and 20.8% with intravenous thrombolysis patients. Symptomatic intracranial haemorrhage occurred solely among endovascular therapy patients (5/38 patients, 13.2%) while four (80%) of these patients had bridging therapy; 6/38 endovascular therapy and 0/24 intravenous thrombolysis patients died. Four of these 6 endovascular therapy patients had bridging therapy. Recanalisation was achieved in 84.2% endovascular therapy patients and 66.7% intravenous thrombolysis patients (odds ratio 3.2, 95% confidence interval [0.9–11.38]). Sensitivity analyses in a subgroup treated within 4.5 h revealed a higher recanalisation rate among endovascular therapy patients (odds ratio 3.87, 95% confidence interval [1.00–14.95]), but no change in the key clinical findings. In a meta-analysis across eight studies (n = 212 patients), cervical artery dissection patients (110 intravenous thrombolysis and 102 endovascular therapy) showed identical odds for favourable outcome (odds ratio 0.97, 95% confidence interval [0.38–2.44]) among endovascular therapy patients and intravenous thrombolysis patients. Discussion and Conclusion: In this cohort study, there was no clear signal of superiority of endovascular therapy over intravenous thrombolysis in cervical artery dissection patients, which – given the limitation of our sample size – does not prove that endovascular therapy in these patients cannot be superior in future studies. The observation that symptomatic intracranial haemorrhage and deaths in the endovascular therapy group occurred predominantly in bridging patients requires further investigation.